Innate Immunity Alterations in Type 2 Diabetes Mellitus: Understanding Infection Susceptibility - de Lourdes Ochoa-González, Fátima; González-Curiel, Irma E.; Cervantes-Villagrana, Alberto R.; Fernández-Ruiz, Julio C.; Castañeda-Delgado, Julio E. (Current Molecular Medicine, 2021)
Diabetes is a chronic disease characterized by marked alterations in the metabolism of glucose and by high concentrations of glucose in the blood due to a decreased insulin production or resistance to the action of this hormone in peripheral tissues. The International Diabetes Federation estimates a global incidence of diabetes of about 10% in the adult population (20 - 79 years old), some 430 million cases reported worldwide in 2018. It is well documented that people with diabetes have a higher susceptibility to infectious diseases and therefore show higher morbidity and mortality compared to the non-diabetic population. Given that the innate immune response plays a fundamental role in protecting against invading pathogens through a myriad of humoral and cellular mechanisms, the present work makes a comprehensive review of the innate immune alterations in patients with type 2 diabetes mellitus (T2D) as well as a brief description of the molecular events leading or associated to such conditions. We show that in these patients a compromised innate immune response increases susceptibility to infections.
Keywords: Type 2 Diabetes Mellitus